Novel vanadium n-propylamino phosphate catalyst: synthesis, characterization and applications - Anumula, Rajini; Nookaraju, Muralasetti; Selvaraj, Kaliaperumal; Reddy, Ingala Ajit Kumar; Narayanan, Venkatathri (Materials Research-Ibero-American Journal of Materials, 2013)
A novel, lamellar type Vanadium n-propylamino phosphate catalyst is synthesized and characterized by using various physicochemical techniques such as Powder X-ray diffraction, Scanning electron microscopy/Energy dispersive X-ray analysis, Thermogravimetry/Differential thermal analysis, Fourier transform Infrared analysis, Electron spin resonance spectroscopy, Ultraviolet - Visible Diffuse reflectance spectroscopy, X-ray Photoelectron spectroscopy, P-31 Magic angle spinning Nuclear Magnetic Resonance spectroscopy and Catalytic applications toward Octahydroquinazolinone synthesis. It is found that the n-propylamine is present as sandwich between Vanadyl phosphate layers. Most of the Vanadium is present as V4+ ions in tetrahedral co-ordination. Vanadium n-propylamino phosphate catalyses Octahydroquinazolinone synthesis more effeciently and the optimum conditions required for Octahydroquinazolinone synthesis are, Benzaldehyde (2 mmol), Dimedone (2 mmol), Urea (4 mmol), Methanol + Water (1:1, 5 mL) and Catalyst (0.05 g). A plausible mechanism is also proposed.
Keywords: n-propylamino phosphate; octahydroquinazolinones; synthesis; Vanadium